2019
DOI: 10.1016/j.forsciint.2019.04.023
|View full text |Cite
|
Sign up to set email alerts
|

From stable isotope ecology to forensic isotope ecology — Isotopes’ tales

Abstract: Highlights Review of applications of stable isotope ecology and forensic stable isotope ecology.  Potential and caveats of isotopic analytical approaches to wildlife forensics are being discussed. Provides information on why differences in stable isotopic composition of a given compound result in measureable differences in its chemical and physical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Forensic science needed biological samples to collect DNA from living things [81], [82] (evenly called wet materials). Several papers reported that they used a bioinformatics approach with high-throughput computing to prove the wildlife trade [17], [70], [83]- [86]. This intelligent computing can prove that genetic evidence-based would explain the wildlife's origin [17], [83].…”
Section: Cases From Forensicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Forensic science needed biological samples to collect DNA from living things [81], [82] (evenly called wet materials). Several papers reported that they used a bioinformatics approach with high-throughput computing to prove the wildlife trade [17], [70], [83]- [86]. This intelligent computing can prove that genetic evidence-based would explain the wildlife's origin [17], [83].…”
Section: Cases From Forensicsmentioning
confidence: 99%
“…Several papers reported that they used a bioinformatics approach with high-throughput computing to prove the wildlife trade [17], [70], [83]- [86]. This intelligent computing can prove that genetic evidence-based would explain the wildlife's origin [17], [83]. Forensics in wildlife (also called wildlife forensics and animal forensics) can be challenging in the following decades in the endangered or CR status of non-human primates (NHPs) species.…”
Section: Cases From Forensicsmentioning
confidence: 99%
“…Stable isotope probing (SIP) technology can be used to track the flow of elements in different substances and organisms in the environment, thus helping scientists infer various chemical reactions or biological processes in nature [91][92][93]. In recent years, nucleic acid (DNA/RNA) detection has been widely combined with SIP technology to link microbial metabolic function with phylogenetic information in environmental samples such as sediment, soil and water [94,95]. The advantage of DNA-SIP technology is that it avoids the deficiency of traditional culture methods and facilitates the identification of target microorganisms by tracking labeled substrates [96].…”
Section: Dna-sipmentioning
confidence: 99%
“…In such cases, it may be more advantageous to source materials from captive animals, to legalize and regulate some trade or to restrict the trade to affected cultures [126]. The use of new technologies, such as the elemental or genetic analyses of animal products, can help regulate such limited trade and prevent the inclusion of illegally wild-caught animals or their body parts into legalized trade [127,128]. It may also be possible to substitute physical symbols with substitutes derived from domesticated birds.…”
Section: Supporting Services To Conservation Where Knowledge and Beli...mentioning
confidence: 99%